Go eat worms! - Stine, R. L. (New York : Scholastic, 1994)
Discovering the creatures of his basement worm farm in unlikely and unwanted places, like his bed, his toothbrush, and his spaghetti, worm-obsessed Todd finds himself grossed out by the very things with which he used to torture his sister.
"An Apple paperback."
570
570
Accelerated Reader AR
Keywords: Horror tales; Worms -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Horror fiction